Novel PLA2G6 Pathogenic Variants in Chinese Patients With PLA2G6-Associated Neurodegeneration - Wan, Yalan; Jiang, Yanyan; Xie, Zhiying; Ling, Chen; Du, Kang; Li, Ran; Yuan, Yun; Wang, Zhaoxia; Sun, Wei; Jin, Haiqiang (Frontiers in Neurology, 2022)
Background: PLA2G6-associated neurodegeneration (PLAN) is a heterogeneous group of neurodegenerative diseases caused by biallelic PLA2G6 mutations, covering diseases such as infantile neuroaxonal dystrophy (INAD), atypical neuroaxonal dystrophy (ANAD), dystonia parkinsonism (DP) and autosomal recessive early-onset parkinsonism (AREP). The study aims to report the clinical and genetic features of a series of PLAN patients. Methods: The clinical and radiological findings of five Chinese patients from three families were collected. Whole-exome next generation sequencing (NGS) was applied to identify the genetic causes. Co-segregation analysis of the detected candidate variants were performed in their families. The pathogenicity of identified novel variants was correspondingly predicted by insilico analysis. Results: NGS revealed compound heterozygous variants of PLA2G6 gene in all five patients. There were six PLA2G6 variants identified, including two known variants (c.116G>A, c.238G>A) and four novel variants (c.2120dupA, c.2071C＞G, c.967G>A, c1534T＞A). c.2120dupA was predicted to be pathogenic by ACMG standards. Clinically, four patients fell into the diagnosis of ANAD, and 1 into the diagnosis of AREP. Brain imaging revealed cerebellar atrophy, and iron deposition in bilateral globus pallidus and substantia nigra were presented in three cases. Conclusions: Four novel pathogenic variants were discovered and the pathogenic variant spectrum of the PLA2G6 gene was expanded.